A longitudinal evaluation of electromagnetic theory students' continuous improvement in learning skills - Rashid, Rozeha A.; Esa, Mazlina; Masodi, Mohd. Saidfudin; Abdullah, R. (IEEE Explore, 2006)
Since 2003, Fakulti Kejuruteraan Elektrik, Universiti Teknologi Malaysia, Skudai subscribed to good practices as required by their teaching and learning processes which was duly certified to ISO 9001:2000. It was developed based on the American Accreditation Board of Engineering and Technology (ABET) requirements which promote the Outcome Based Education (OBE) learning process. Collaborative and cooperative learning (CCL) technique was applied to inculcate the necessary generic skills attributes. A series of assessment were designed to validate such learning outcomes. Final exam questions were evaluated using Bloom's Taxonomy. The tests employed include index of difficulty and index of discrimination. This paper presents a longitudinal evaluation based on a case study conducted on an undergraduate microwave engineering course for four consecutive years, with specific reference to repeat students' achievements for session 2004/05-2 and the consecutive 2005/06-1. It was found that correlation exists between the effectiveness of CCL and significantly improved students' performance.